2016
DOI: 10.5751/es-08849-210430
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating credibility and legitimacy in the shadow of an authoritative data source

Abstract: ABSTRACT. Environmental agencies designate certain datasets as "authoritative," or official datasets for use in decision making. Although this is a common administrative term, the notion of certain sources being authoritative has received minimal attention in the social science literature. Science translates into environmental decisions when it is perceived as being salient, credible, and legitimate. But the actual process by which data come to be viewed as credible and legitimate has received little attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Similar to our stakeholder process, collaborative governance involves constructively engaging people in decision-making across the boundaries of public agencies, levels of government, and the public, private, and civic spheres [50]. Research on perceptions of trust and credibility demonstrate that science translates into environmental decision-making when it is perceived to be salient, credible, and legitimate [51]. Ultimately, the CBPR approach undertaken to develop the DWT as an environmental justice tool represents an important step toward actually achieving the Human Right to Water.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our stakeholder process, collaborative governance involves constructively engaging people in decision-making across the boundaries of public agencies, levels of government, and the public, private, and civic spheres [50]. Research on perceptions of trust and credibility demonstrate that science translates into environmental decision-making when it is perceived to be salient, credible, and legitimate [51]. Ultimately, the CBPR approach undertaken to develop the DWT as an environmental justice tool represents an important step toward actually achieving the Human Right to Water.…”
Section: Discussionmentioning
confidence: 99%
“…Several coauthors on this paper have experience with drought planning. One point they made consistently was that the planning process itself is important; it can serve dual decision making and social learning functions (Cravens & Ardoin, 2016;Cundill et al, 2010). Generating a long list of impacts might be valuable as part of the process of maintaining communication, soliciting input, and educating stakeholders about the concerns of other community members.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that the information is considered trustworthy, researchers need to be transparent about data collection, interpretation and Cravens and Ardoin (2016) concluded that trust in scientific information is not so much a characteristic of the information itself or of the way it has been generated, but rather the outcome of a process of discussion and social learning in which scientists and practitioners take part. To improve the level of trust in spatial information, actors in a workshop can be asked whether they recognize the information on a map being consistent with their own experience.…”
Section: Key Factors For Navigating the Science-practice Spacementioning
confidence: 99%